A systematic review of the role of re-laparoscopy in the management of complications following laparoscopic colorectal surgery. Issue 5 (October 2016) - Chang, K.H.; Bourke, M.G.; Kavanagh, D.O.; Neary, P.C.; O'Riordan, J.M.
Abstract: The benefits of laparoscopic versus open surgery for patients with both benign and malignant colorectal disease have been well established. Re-laparoscopy in patients who develop complications following laparoscopic colorectal surgery has recently been reported by some groups and the aim of this systematic review was to summarise this literature. A literature search of PubMed, Medline and EMBASE identified a total of 11 studies that reported laparoscopic re-intervention for complications in 187 patients following laparoscopic colorectal surgery. The majority of these patients required re-intervention in the immediate postoperative period (i.e. less than seven days). Anastomotic leakage was the commonest complication requiring re-laparoscopy reported (n = 139). Other complications included postoperative hernia (n = 12), bleeding (n = 9), adhesions (n = 7), small bowel obstruction (n = 4), colonic ischaemia (n = 4), bowel and ureteric injury (n = 3 respectively) and colocutaneous fistula (n = 1). Ninety-seven percent of patients (n = 182) who underwent re-laparoscopy had their complications successfully managed by re-laparoscopy, maintaining the benefits of the laparoscopic approach and avoiding a laparotomy. We conclude that re-laparoscopy for managing complications following laparoscopic colorectal surgery appears to be safe and effective in highly selected patients.